STUDY OF ELECTROCHEMICAL BEHAVIOR AND DEPOSIT MORPHOLOGY OF COPPER FROM ELECTROWINNING PROCESS UNDER VARIATION OF LIGNIN-BASED BIOPOLYMER ADDITIVE - Sabdho Illahi, Gelar
There have been everal problems faced in the copper electrowinning process. One of the problems is short circuit that can significantly reduce electrowinning process performance. One of the inducing factors of short circuit is the growth of nodule or dendrite on the copper deposit. Several additive with certain dosage is needed to be added in the electrolyte for preventing the earlier mentioned problem. Chloride ion, thiourea, and glue is the common additives used in the industrial application of copper electrowinning and electrorefining. There is a problem is which glue is easily to degrade in the high temperature and high acidity of electrolyte solution. In this research, performance of new additive of a lignin-based biopolymer with the code of DP4400 is studied. The additive performance is investigated by evaluating the cathode electrochemical behavior and the deposit morphology. The cathode electrochemical behavior is analysed by conducting potentiodynamic and galvanostatic measurements under variations of additive concentration by using a potentiostat. The behavior of additive degradation was studied by heating the electrolyte added with the additive at a temperature of 45C for up to 24 hours followed by galvanostatic measurements after the solution was exposed for 4, 12 and 24 hours at 45?C. A series of electrolysis experiments were also carried out for 12 hours to determine the quality of the deposits produced by the addition of lignin-based biopolymer additives with various concentrations. The experiment results show that lignin-based DP4400 biopolymer additive (in single or combined with thiourea) gave polarizing effect on cathode during copper deposition. The combination with thiourea reduced the polarizing effect of DP4400. The results of the additive degradation test showed that the glue degraded after heating for 4 hours and its cathodic polarizing effect disappeared after 24 hours of heating. Meanwhile, thiourea and DP4400 showed their stability as indicated by the polarization behavior of the cathode which tended not to change significantly after being heated for 24 hours. The results of the 12 hour electrolysis experiment with the addition of the additive of 30 mg/L DP4400 resulted in a flat and smooth deposit similar to the deposit produced by the electrolysis with additives of glue-thiourea combination. The use of the DP4400 additive provides a current efficiency of> 98.4% and an energy consumption ranging from 3.47-3.78 kWh/kg of deposit..